From Model Minority to Yellow Peril: The Shifting Narratives of Asian International Students - Liu, Helen (Journal of International Students, 2022)
The ongoing pandemic, COVID-19, has demonstrated how quickly the depictions of Asian individuals can shift from “model minority” to “yellow peril” during times of crisis. These times were particularly difficult for Asian post-secondary international students who were directly impacted by these shifting narratives, as many faced discrimination, violence, and prejudice as a result of the rise of anti-Asian hate that occurred across Canada. Thus, utilizing Critical Race Theory (CRT), the purpose of this article is to provide an overview of these contrasting narratives and how “model minority” and “yellow peril” can contribute to the maintenance of White supremacy, and possible considerations and interventions to better support Asian international post-secondary students during their studies in Canada.